2020
DOI: 10.3390/ani10081362
|View full text |Cite
|
Sign up to set email alerts
|

Association between Single Nucleotide Polymorphisms in SIRT1 and SIRT2 Loci and Growth in Tibetan Sheep

Abstract: Silent information regulator 1 and 2 (SIRT1, 2) were NAD+-dependent histone or non-histone deacetylase, which emerged as key metabolic sensors in several tissues of mammals. In the present study, the search for polymorphisms within the ovine SIRT1 and SIRT2 loci as well as association analyses between SNPs and growth-related traits were performed in Tibetan sheep. To determine the expression pattern of SIRT1 and SIRT2 genes in Tibetan sheep, the quantitative real-time polymerase chain reaction (qPCR) analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Present studies are mainly focused on improving the meat quality and growth performance of Tibetan sheep. Previous studies have identified the gene FGFR1 to be involved in the growth-related traits, and henceforth, it was used as the genetic marker for improving the growth traits of the Tibetan sheep (3) The polymorphisms in SIRT1 and SIRT2 regulate the growth-related traits in Tibetan sheep (4). The quantitative genetic analysis revealed IRS1 to be associated with the growth-efficiency traits possibly useful for markerassisted selection in Chinese indigenous sheep (5).…”
Section: Introductionmentioning
confidence: 99%
“…Present studies are mainly focused on improving the meat quality and growth performance of Tibetan sheep. Previous studies have identified the gene FGFR1 to be involved in the growth-related traits, and henceforth, it was used as the genetic marker for improving the growth traits of the Tibetan sheep (3) The polymorphisms in SIRT1 and SIRT2 regulate the growth-related traits in Tibetan sheep (4). The quantitative genetic analysis revealed IRS1 to be associated with the growth-efficiency traits possibly useful for markerassisted selection in Chinese indigenous sheep (5).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, following the development of biotechnology and genome research, an increasing number of SNPs related to the growth traits of livestock and poultry have been discovered. Studies have shown that the g.3148C > T polymorphism of the SIRT1 gene affects the heart circumference of Tibetan sheep, and the g.8074 T > A polymorphism of the SIRT2 gene is significantly correlated with body weight and body length ( 40 ). Cao et al discovered OARX_76354330.1 and s64890.1 to be functional SNPs for growth traits of Hu sheep through genome-wide association analysis of body weight and identified three candidate genes related to body weight in Hu sheep ( 41 ): CAPN6 , ITGA11 and SCMH1 .…”
Section: Discussionmentioning
confidence: 99%
“…The recent availability of genome-wide SNPs gave a new momentum to identify the genetic variants underlying phenotypic traits ( Kijas et al, 2012 ; Xu and Li 2017 ; Gui et al, 2020 ; Abousoliman et al, 2021 ; Zhou et al, 2021 ). Previous studies have identified a number of candidate genes or variants associated with meat, growth, milk, wool, reproduction, horns and tails in sheep, most of which have employed the low-density SNPs (50K) (see the review in Xu and Li, 2017 ) or whole-genome sequences ( Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%